Analysis of the Influence of Obedience to Accounting Rules, Employee Motivation and Management Morality on the Tendency of Accounting Fraud - Luciana Borolla; Fanny Monika Anakotta; Adonia Anita Batkunde (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to test empirically the effect of complying with accounting rules, employee motivation and management morality on the tendency of accounting fraud with quantitative research methods. The object is the variable used in the study. The object of this research is the tendency of accounting fraud, obedience to accounting rules, employee motivation and management morality. The data collection technique used is through sending questionnaires to respondents. The data analysis technique used is quantitative data analysis technique using multiple linear regression analysis. The results of this study indicate that compliance with accounting rules and management morality has a significant negative effect on the tendency of accounting fraud, while employee motivation has no significant effect on the tendency of accounting fraud.